PENGARUH LATIHAN HARNESS TERHADAP KECEPATAN PEMAIN SEPAK BOLA U-17 KOTO BARU SOCCER PAYAKUMBUH - Muhammad Alfadil; Didin Tohidin; Ridho Bahtra; Pudia M Indika (Jurnal IKEOR, 2023)
The problem in this study is that it is suspected that the running speed of Koto Baru Soccer Payakumbuh soccer players is still not good. This study aims to determine the effect of weight running training on the speed of Koto Baru Soccer Payakumbuh soccer players.This research is included in the type of pseudo-experimental research, with the research design "One group preetest posttest design". The population in this study were 20 Koto Baru Soccer soccer players. In this study using the "total sampling" technique. This study uses its research instruments, namely: a 40-meter running test to measure acceleration speed by Endang Sepdanius (2019).Based on difficult data analyzed using the T test, the results showed that: "there is an effect of weight running training on the speed of Koto Baru Soccer Payakumbuh soccer players". The above can be proven by the obtained Thitung value of 2.533 and Ttabel of 1.724 means Thitung> Ttabel (2.533> 1.742). There is an average preetest (initial test) of 7.11 and an average posttest (final test) of 6.68. Then the data can be said to be acceptable. Thus H0 is rejected and Ha means that there is an effect of weight running training on the speed of Koto Baru Soccer Payakumbuh soccer players.